Dynamic security assessment by fuzzy inference - Manuel António Cerqueira da Costa Matos (1999)
This paper reports an experience on the application of fuzzy reasoning to the fast assessment of the dynamicsecurity of an isolated power system with high wind power penetration. The inference method is a TakagiSugenotype system with a small number of rules, optimized for each specific learning set by a standard methodincluded in the MATLAB Fuzzy Logic Toolbox. The methodology is demonstrated in a contingency study in thenetwork of Crete that showed good results in the test set. The paper discusses some implementation issues andpossible future developments of the approach.